2023
DOI: 10.1002/jctb.7456
|View full text |Cite
|
Sign up to set email alerts
|

Phenol and nitrogen removal in microalgal–bacterial granular sequential batch reactors

Abstract: BACKGROUND: Microalgal-bacterial systems work on the principle of the symbiotic relationship between algae and bacteria. The ability of algal-bacterial photobioreactors for the treatment of wastewater containing ammonia and phenol has been poorly addressed. In this work a self-sustaining synergetic microalgal-bacterial granular sludge process was thus developed to treatment of industrial wastewater based upon the low cost of photosynthetic oxygenation and the simultaneous phenol and nitrogen removal. The perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…Yasmeen [19] indicated that an algal membrane photobioreactor (MPBR) will be helpful in either supplying the O 2 by recirculating the O 2 -rich effluent produced into the MBR or improving water quality by reducing the nutrients before entering into the MBR. Bucci et al [20] compared the effect of a bacterial aerobic granular sludge SBR and bacterial and algal aerobic granular sludge on the removal of phenol and ammonia nitrogen. They found that the phenol removal rate reached 100% in 24 h and the NH 4 + -N removal rate of bacterial aerobic granular sludge SBR was 100%, while the NH 4 + -N removal rate of bacterial aerobic granular sludge SBR was 0.5%.…”
Section: Closed Bacteria-algae-biofilm Photobioreactormentioning
confidence: 99%
“…Yasmeen [19] indicated that an algal membrane photobioreactor (MPBR) will be helpful in either supplying the O 2 by recirculating the O 2 -rich effluent produced into the MBR or improving water quality by reducing the nutrients before entering into the MBR. Bucci et al [20] compared the effect of a bacterial aerobic granular sludge SBR and bacterial and algal aerobic granular sludge on the removal of phenol and ammonia nitrogen. They found that the phenol removal rate reached 100% in 24 h and the NH 4 + -N removal rate of bacterial aerobic granular sludge SBR was 100%, while the NH 4 + -N removal rate of bacterial aerobic granular sludge SBR was 0.5%.…”
Section: Closed Bacteria-algae-biofilm Photobioreactormentioning
confidence: 99%
“…In recent years, the environmental hazards caused by textile and dyeing industry wastewater have been increasing, which is mainly reflected in the fact that the wastewater produced not only destroys the natural environment but also flows into residential areas. Especially, dyestuff wastewater is difficult to decompose naturally and exists for a long term in the ecological cycle, which causes skin or respiratory diseases and damages human health. In order to remedy the worsening water environment, many treatments, including physical adsorption, , microbiological degradation, electrocatalytic degradation, and photocatalyst degradation, were used to treat dyestuff wastewater. Among them, the photocatalysis technology is gaining significant attention as a clean and energy-saving method. , The key limitation to the large-scale application of the photocatalysis technology is the lack of inexpensive, safe, and high-efficiency photocatalysts.…”
Section: Introductionmentioning
confidence: 99%